2006
DOI: 10.1073/pnas.0600509103
|View full text |Cite
|
Sign up to set email alerts
|

G protein βγ-subunits activated by serotonin mediate presynaptic inhibition by regulating vesicle fusion properties

Abstract: Neurotransmitters are thought to be released as quanta, where synaptic vesicles deliver packets of neurotransmitter to the synaptic cleft by fusion with the plasma membrane. However, synaptic vesicles may undergo incomplete fusion. We provide evidence that G protein-coupled receptors inhibit release by causing such incomplete fusion. 5-hydroxytryptamine (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
90
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(97 citation statements)
references
References 47 publications
7
90
0
Order By: Relevance
“…In this work it has been shown that inhibition of exocytosis by PGE 1 is abolished by a high level of Ca 2+ influx in accord with previous reports that increased Ca 2+ overcomes both serotonininduced inhibition of neurotransmitter release , Gerachshenko et al 2005, Photowala et al 2006 and NE-induced inhibition of insulin release (Zhao et al 2010b). The inhibition of release by serotonin and NE is mediated by heterotrimeric G-protein βγ subunits that block the binding of synaptotagmin to SNAP25 and thereby block SNARE protein function and exocytosis.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…In this work it has been shown that inhibition of exocytosis by PGE 1 is abolished by a high level of Ca 2+ influx in accord with previous reports that increased Ca 2+ overcomes both serotonininduced inhibition of neurotransmitter release , Gerachshenko et al 2005, Photowala et al 2006 and NE-induced inhibition of insulin release (Zhao et al 2010b). The inhibition of release by serotonin and NE is mediated by heterotrimeric G-protein βγ subunits that block the binding of synaptotagmin to SNAP25 and thereby block SNARE protein function and exocytosis.…”
Section: Discussionsupporting
confidence: 89%
“…This distal inhibition of exocytosis in β-cells is similar to that in the central nervous system where serotonin inhibits neurotransmitter release downstream of increased [Ca 2+ ] i (Blackmer et al 2001) and in pituitary lactotrophs where endothelin blocks prolactin release; also downstream of elevated [Ca 2+ ] i (Andric et al 2005). The mechanism involves G βγ blockade of syntaxin binding to SNAP25 , Gerachshenko et al 2005, Photowala et al 2006. Although it was once believed that all physiological inhibitory effects on the β-cells were mediated by the Pertussis toxinsensitive (PTX)-sensitive heterotrimeric G i and G o proteins (Komatsu et al 1995), it has been reported that inhibition of adenylyl cyclase by PGE 1 is mediated via G z (Kimple et al 2005(Kimple et al , 2008.…”
Section: Introductionmentioning
confidence: 63%
See 2 more Smart Citations
“…CB 1 Rs are G protein-coupled receptors linked to pertussis-sensitive Gi/o α subunits. Activation of the α subunit triggers dissociation of the βγ complex, which reduces adenylate cyclase production of cyclic adenosine monophosphate [48], inhibits N-and P/Qtype voltage-gated calcium channels [31,[49][50][51][52], stimulates Atype potassium channels [53][54][55][56], activates G protein-coupled inwardly-rectifying potassium channels [57][58][59], and inhibits the vesicular release machinery [60]. These multiple mechanisms reduce presynaptic cell excitability and Ca 2+ , strongly diminishing presynaptic neurotransmitter release.…”
Section: The Endocannabinoid Systemmentioning
confidence: 99%